Study of Reading Abilities in Primary School Children - Kiran Shenoy (Journal of All India Institute of Speech and Hearing, 1970)
Tests of oral reading and reading comprehension have been one of the earliest and most frequently used tools of reading assessment. They also,usually form a regular feature of test batteries of reading assessment.